Lepus (Lepus) arcticus subsp. arcticus Ross 1819 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Lepus (Lepus) arcticus subsp. arcticus Ross 1819 Lepus (Lepus) arcticus subsp. arcticus Ross 1819, Voy. Discovery, II; ed. 2, App. IV: 170. Type Locality: "Southeast of Cape Bowen" (Nelson, 1909:61) [Possession Bay, Bylot Island, lat. 73E37'N, Canada]. Synonyms: Lepus (Lepus) arcticus subsp. andersoni Nelson 1934; Lepus (Lepus) arcticus subsp. banksicola Manning and Macpherson 1958; Lepus (Lepus) arcticus subsp. canus Preble 1902; Lepus (Lepus) arcticus subsp. glacialis Leach 1819. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Lagomorpha, pp. 185-211 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 195, DOI: 10.5281/zenodo.7316519